How Does Perceived Value Affect Satisfaction in the Pujon Kidul Tourism Village Through Their Experience? - Kristiawan, Andreas Tri Purnomo Hijrah; Iqbal, Mohammad; Faisal Riza, Muhammad (Profit: Jurnal Adminsitrasi Bisnis, 2025)
Value perception is divided into two aspects: functional and emotional. Both values ​​are thought to influence tourist satisfaction. Value perception certainly does not stand alone but is accompanied by the quality of the tourist experience. Both variables are continuous, linking the causal relationship between stimulus value perception and the response felt through the quality of experience. This study aims to determine the relationship between variables in value perception to experience and visitor satisfaction in Pujon Kidul Tourism Village. Using a descriptive quantitative method, this study collected data from 250 respondents who were visitors to Pujon Kidul Tourism Village through a questionnaire. The data collected were then processed using the SEM-PLS method. The results indicate that the perception of value, encompassing both emotional and functional aspects, positively impacts the quality of the visitor experience. The perception of value, both emotional and functional, has a positive impact on visitor satisfaction in Pujon Kidul Tourism Village. Meanwhile, the quality of visitor experience positively affects visitor satisfaction. This indicates that the quality of visitor experience has successfully mediated the relationship between value perception and visitor satisfaction.